Ang mga Mangyan ng Mindoro ([Manila Asian Social Institute Communication Center], 1978)
A production about the "open letter" signed by the thumbprints of 200 Mangyan representatives, as a plea for land that is rightfully theirs.
Keywords: Ethnic group; Minorities; Philippine history